2014
DOI: 10.1016/j.jinorgbio.2014.07.001
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclopalladated and cycloplatinated benzophenone imines: Antitumor, antibacterial and antioxidant activities, DNA interaction and cathepsin B inhibition

Abstract: The antitumor, antibacterial and antioxidant activity, DNA interaction and cathepsin B inhibition of cyclo-ortho-palladated and -platinated compounds [Pd(C,N)]2(μ-X)2 [X=OAc (1), X=Cl (2)] and trans-N,P-[M(C,N)X(PPh3)] [M=Pd, X=OAc (3), M=Pd, X=Cl (4), M=Pt, X=Cl (5)] are discussed [(C,N)=cyclo-ortho-metallated benzophenone imine]. The cytotoxicity of compound 5 has been evaluated towards human breast (MDA-MB-231 and MCF-7) and colon (HCT-116) cancer cell lines and that of compounds 1-4 towards the HCT-116 hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…A notable potency for a highly cytotoxic coordination compound containing two non-cyclometallated amine ligands [58] has been observed in our research group. On the other hand, we have also reported that a series of cyclopalladated and cycloplatinated benzophenone imines were not efficient inhibitors of cathepsin B, although showing in vitro high cytotoxicity [59]. a The enzyme was preincubated for 2 h with each compound (from 5 to 100 µM).…”
Section: Cathepsin B Inhibitionmentioning
confidence: 99%
“…A notable potency for a highly cytotoxic coordination compound containing two non-cyclometallated amine ligands [58] has been observed in our research group. On the other hand, we have also reported that a series of cyclopalladated and cycloplatinated benzophenone imines were not efficient inhibitors of cathepsin B, although showing in vitro high cytotoxicity [59]. a The enzyme was preincubated for 2 h with each compound (from 5 to 100 µM).…”
Section: Cathepsin B Inhibitionmentioning
confidence: 99%
“…At T 660 nm and T 280 nm, the neat CMC and gelatin films had transmittance values of 87.2 ± 0.50, 90.7 ± 0.15, 58.3 ± 1.25, and 30.4 ± 1.50, respectively. When ZnO-Nps was added to CMC/gelatin blend, the percentage transmittance of films at 280 nm was drastically reduced, falling to just 0.3%, whereas the percentage transmittance values at 660 nm only slightly decreased as ZnO-Nps concentrations were increased [ 35 ]. The amount of ZnO-Nps present had a significant impact on the transmittance value of the nanocomposite films.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of ZnO nanoparticles has increased the elongation at break, and tensile strength values for the CMC/GEL films to 44.6 MPa and 10%, respectively. The increased tensile strength of CMC/gelatin films may be attributed to the incorporation of the proper amount of nanoparticles as well as the bonding between hdroxy groups of gelatin and the hydrophilic groups of CMC, resulting in the formation of a mechanically stable nanocomposite between CMC, gelatin, and zinc oxide nanoparticles [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34,36,38,43,44] The synthesized Schiff bases exhibited comparable or lower MIC values compared to other heterocyclic imine families. [27,38,39,45,46] The results obtained against Gram-negative and Gram-positive bacteria demonstrate the broad-spectrum antibacterial activity of these newly synthesized compounds, which could be mediated through multiple mechanisms targeting essential bacterial growth steps. Previous publications suggest that these mechanisms include the inhibition of crucial metabolic enzymes in the target microorganism, interference with cell wall synthesis, destruction of specific microbial cellular proteins, and alteration of normal cellular processes.…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 87%